Reproduction of species of the genus Cichla in a reservoir in Southeastern Brazil - Gomiero, L. M. [UNESP]; Braga, Francisco Manoel de Souza [UNESP] (Instituto Internacional de Ecologia, 2004)
Foi analisada a reprodução das espécies de tucunarés (Cichla cf. ocellaris e Cichla monoculus) introduzidas no reservatório de Volta Grande, Sudeste do Brasil. A época das desovas teve início no final do período de seca (setembro) e estendeu-se até o final do período chuvoso (janeiro). O comprimento da primeira maturação gonadal (L50) e o comprimento a partir do qual os peixes dessas espécies são considerados adultos (L100) foram muito próximos e coincidem com os comprimentos de peixes com um ano de vida. A análise dos ovócitos dissociados evidenciou a desova parcelada, sendo C. monoculus mais prolífico do que C. cf. ocellaris. A baixa fecundidade, a desova parcelada, o cuidado biparental e o suprimento de alimento para os jovens estão relacionados ao modo de vida, ao habitat e ao comportamento reprodutivo desses peixes.

The reproduction of two species of Cichla (Cichla cf. ocellaris and C. monoculus, commonly known in Brazil as tucunaré) introduced in the Volta Grande Reservoir, southeastern Brazil, was analyzed. The period for spawning began at the end of the dry season (September) and extended until the end of the rainy season (January). The length of the first gonad maturation (L50) and the length at which all fish are considered adults (L100) were very similar for both species and coincide with the length of fish at one year of age. The analysis of disassociated oocytes evidenced a partitioned spawning, and that C. monoculus was more prolific than C. cf. ocellaris. The low fecundity, partitioned spawning, bi-parental brood care, and supplying of food for the young are related to the way of life, habitat, and reproductive behavior of these fish.
Reprodução de espécies de Cichla em um reservatório do Sudeste do Brasil
Keywords: Cichla; reprodução; fecundidade; reservatório; Brasil; Cichla; reproduction; fecundity; reservoir; Brazil